Comparison of Microleakage of Composite and Glass Ionomer Restorations in Primary Molars Pretreated with Silver Diamine Fluoride at Two Time Intervals: An In Vitro study - Mais Zubair Jasim; Muna Saleem Khalaf (Dental Hypotheses, 2022)
Introduction: We aimed to evaluate the microleakage of composite resin and self-cure glass ionomer (GI) restorations in primary molars when the restorations were applied at the same day of silver diamine fluoride (SDF) treatment, and after 14 days. Methods: Class V cavities made at the buccal surface of 64 deciduous molars. For the experimental group of 32 teeth treated with SDF (eight teeth filled with composite and eight teeth filled with GI after 1 day and 14 days), the remaining 32 teeth without application of SDF served as a control group. All samples were then thermocycled and immersed in 2% methylene before being molded in epoxy resin to facilitate cutting into two sections. The dye penetration was then measured using a stereomicroscope at 20× magnification. Results: Overall model test showed statistical significant difference among study groups (P < 0.001). Post hoc test showed significant difference for usage of silver diamine fluoride (P < 0.001) and non-significant differences for type of restoration (P = 0.21) and time (P = 0.43). Conclusion: There was a significant reduction in microleakage following the usage of SDF before restoration over time.